Handover Management for Drones in Future Mobile Networks—a Survey - Ibraheem Shayea; Pabiola Dushi; Mohammed Banafaa; Rozeha A. Rashid; Sawsan Ali; Mohd Adib Sarijari; Yousef Ibrahim Daradkeh; Hafizal Mohamad (MDPI, 2024)
Indexed by WOS/Scopus/ERA